2002
DOI: 10.4049/jimmunol.169.12.7009
|View full text |Cite
|
Sign up to set email alerts
|

Repression ofrac2mRNA Expression byAnaplasma phagocytophilaIs Essential to the Inhibition of Superoxide Production and Bacterial Proliferation

Abstract: Anaplasma phagocytophila, the etiologic agent of human granulocytic ehrlichiosis, is an emerging bacterial pathogen that invades neutrophils and can be cultivated in HL-60 cells. Infected neutrophils and HL-60 cells fail to produce superoxide anion (O2−), which is partially attributable to the fact that A. phagocytophila inhibits transcription of gp91phox, an integral component of NADPH oxidase. cDNA microarray and RT-PCR analyses demonstrated that transcription of the gene encoding Rac2, a key component in NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 63 publications
6
123
4
Order By: Relevance
“…In contrast, there are immediate (within 30 min) and dramatic increases in neutrophil Second, our data clearly demonstrate that genes encoding components of NADPH oxidase, including gp91 phox and Rac2, remain unchanged or are up-regulated in human neutrophils during A. phagocytophilum infection (Table I). These results are at variance with previous studies that suggest the inability of PMNs to produce ROS production following uptake of A. phagocytophilum is due to decreased gp91 phox and/or Rac2 transcript levels (12,14). However, those studies were limited in scope and/or used HL60 cells rather than human PMNs (12,14).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…In contrast, there are immediate (within 30 min) and dramatic increases in neutrophil Second, our data clearly demonstrate that genes encoding components of NADPH oxidase, including gp91 phox and Rac2, remain unchanged or are up-regulated in human neutrophils during A. phagocytophilum infection (Table I). These results are at variance with previous studies that suggest the inability of PMNs to produce ROS production following uptake of A. phagocytophilum is due to decreased gp91 phox and/or Rac2 transcript levels (12,14). However, those studies were limited in scope and/or used HL60 cells rather than human PMNs (12,14).…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, none of the genes encoding NADPH oxidase components, including CYBB (gp91 phox ) and CYBA (p22 phox ), were significantly down-regulated after A. phagocytophilum infection (Table I). These results clearly indicate that failure of A. phagocytophilum to elicit production of ROS by PMNs, or to block ROS production by a second stimulus, is not due to repression of genes encoding NADPH oxidase proteins, as previously suggested (12)(13)(14)(15).…”
Section: Expression Of Genes Encoding Nadph Oxidase Componentssupporting
confidence: 58%
See 2 more Smart Citations
“…We previously demonstrated that IL-1␤ and IL-18 were up-regulated when A. phagocytophilum infects neutrophils and promyelocytic cells (3,7,8). Some Nod-like receptors (NLR) 3 have been shown to regulate IL-1␤ and IL-18 secretion (9 -13).…”
mentioning
confidence: 99%